P6.23 ARTERIAL STIFFNESS MEASUREMENT IN OBESE PATIENTS WITH A NEW DEVICE: POPMETRE® - M. Hallab; A. Compaore; K. Mohammedi; F. Travert; M. Marre (Artery Research, 2013)
Introduction: Obesity is associated with increased cardiovascular morbidity and mortality. Arterial stiffness (AS) is an independent cardiovascular risk factor. The objective of this study was to evaluate the SA in obese patients. Patients and methods: AS was measured in 212 participants divided into four groups: non-obese non-diabetic controls (n=114). non-diabetic subjects with obesity (n=37), obese and type 2 diabetic patients (n=34), non-obese type 2 diabetic subjects (n=27). AS was assessed by measuring the pulse wave velocity (PWV) using a new device: pOpmètre® (Axelife sas-France) at the right and the left side. Results: PWV values were increased in obese subjects compared to controls (obese and diabetic patients: 18.18±1.08, non-diabetic obese subjects: 11.32±1.04, non-obese diabetic patients: 15.58±1.21 and controls: 8.39±0.59 m/s, mean±SEM, p<0.001). Similar results were observed in the left side (p=0.0005). This increase was more pronounced in obese and diabetic patients. After stratification on the presence of diabetes, we observed an increase of PWV in non-obese diabetic patients, compared to non-diabetic subjects (p=0.001 and 0.0001). Stratification on the presence of obesity shown no difference in non-diabetic obese subjects compared to non-obese subjects. Adjustment for sex, age, blood pressure and tobacco, confirmed the increase of PWV in obese and diabetic patients compared to controls (odds ratio: 1.31, 95% CI 1.15–1.51, p=0.0002) and increased PWV in non-diabetic obese subjects compared to controls (odds ratio: 1.25, 95% CI 1.09–1.46, p=0.003). We observed a positive correlation between age and PWV (r2=0.24 and 0.25, for right and left limbs). Conclusion: PWV is increased in obese patients, particularly in those with type 2 diabetes. PWV is positively correlated to ageing.